قراءة في كتاب مالك بن نبي (المسلم في عالم الاقتصاد) = Muslim in the world of economics (Malek Bennabi): an attempt for a contemporary understanding - Nasser, Youcef (Hankuk University of Foreign Studies, Seoul- Republic of Korea, 2023)
This study deals with analysis toward the writing of Malek Bennabi entitled Submission to the World of Economics after passing fifty years of publication which is characterized with distinction. This study also discusses about the domain of knowledge and ideological background of Malek Bennabi particularly pertains to Islamization and innovative contribution toward social adaptation related to the experience of China in economy. We analyze the view of Malek Bennabi in the sense that he is an ideal academician in the world of economics related with ethical and intellectual. This kind of vision leads to the query whether his thought on the issue of economy remains significant to reform the world of economics.